2016
DOI: 10.1111/asap.12124
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Differences in the Role of Economic Competitiveness in Prejudice toward Immigrants and Foreign Workers

Abstract: This study investigated cultural differences in the role of economic competitiveness in prejudice toward immigrants and foreign workers betweenNorthern Europeanheritage and East Asian cultures. Because economic competitiveness and achievement are associated with core cultural values in Northern European-heritage cultures, we hypothesized that economic competitiveness would be associated with prejudice toward immigrants and foreign workers more strongly in Northern European-heritage than in East Asian cultures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 49 publications
(114 reference statements)
1
8
0
Order By: Relevance
“…Not only does this distinction relate to a larger debate about the impact of nature versus nurture attribution for psychological phenomena and the consequences of these attributions (see also Rangel & Keller, 2011), but also it more narrowly relates to the justification for the perceived stability of intergroup hierarchies. For instance, the endorsement of social hierarchies in the US was predicted by the emphasis on individual achievements, a core cultural value of NEH cultures that emphasize personal choice (Markus, Mullally, & Kitayama, 1997) and consequent capitalistic/meritocratic achievements (Schwartz, 1992, 1994; Shin & Dovidio, 2016; see also Weber, 1905). The value of individual achievements in NEH cultures, combined with the tendency to attribute outcomes to person-related factors in NEH cultures (the “fundamental attribution error,” Ross, 1977; see also the “correspondence bias,” Choi & Nisbett, 1998; Gilbert & Malone, 1995; Morris & Peng, 1994), can provide culturally acceptable justifications for social hierarchies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not only does this distinction relate to a larger debate about the impact of nature versus nurture attribution for psychological phenomena and the consequences of these attributions (see also Rangel & Keller, 2011), but also it more narrowly relates to the justification for the perceived stability of intergroup hierarchies. For instance, the endorsement of social hierarchies in the US was predicted by the emphasis on individual achievements, a core cultural value of NEH cultures that emphasize personal choice (Markus, Mullally, & Kitayama, 1997) and consequent capitalistic/meritocratic achievements (Schwartz, 1992, 1994; Shin & Dovidio, 2016; see also Weber, 1905). The value of individual achievements in NEH cultures, combined with the tendency to attribute outcomes to person-related factors in NEH cultures (the “fundamental attribution error,” Ross, 1977; see also the “correspondence bias,” Choi & Nisbett, 1998; Gilbert & Malone, 1995; Morris & Peng, 1994), can provide culturally acceptable justifications for social hierarchies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Rangel and Keller (2011) found that the degree to which German participants endorsed the Protestant ethic was associated with beliefs about social determinism but not with beliefs about genetic determinism. Protestant ethic is a core cultural value of NEH culture that emphasizes personal diligence and encourages individual achievements including individual wealth (Weber, 1905; see also Shin & Dovidio, 2016). Their results imply that the value of individual achievements may be associated with the emphasis on social qualities more strongly than the emphasis on biological qualities in NEH cultures.…”
Section: Socially- and Biologically-based Intergroup Hierarchy Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has generally emphasized basic, and often assumed to be universal, psychological influences that contribute to prejudice toward immigrants and foreign workers (e.g., perceived realistic conflicts; Esses, Jackson, Dovidio, & Hodson, ). However, prejudice toward immigrants and foreign workers may also be affected by specific norms and values that can vary across countries and cultures (Shin & Dovidio, ). For example, the relationship between conceptions of national identity and attitudes toward immigrants differs between Canada and Germany (Esses, Wagner, Wolf, Preiser, & Wilbur, ).…”
mentioning
confidence: 99%
“…We compared the United States (U.S.), Germany, and Australia. These three countries are among the major immigrant‐receiving nations (United Nations International Migrant Report, 2017) and share a Northern European‐heritage culture, which emphasizes individualism (Triandis, ) and the Protestant work ethic and capitalism (Shin & Dovidio, ). However, these countries differ on a range of demographic and societal dimensions and in historical and contemporary political orientations toward immigrants and foreign workers.…”
mentioning
confidence: 99%